Land transfer, registration of deeds and title - Maguire, Joseph (Statistical and Social Inquiry Society of Ireland, 1923)
The aim of this paper is to outline the history and characteristics of the two systems [land titles and land deeds], showing the advantages as well as the drawbacks of each with the view to the improvement of both, that ultimately titles may be simplified and secured, their transfer cheapened and expedited as far as may be possible, so that land may become more marketable than it is at present and better appreciated as a security for money.
Read February 17th, 1922.
Keywords: Land registration; Titles and deeds; 314.15